An introduction to ocean remote sensing - Martin, Seelye, 1940- (Cambridge : Cambridge University Press, 2014)
Fully updated, with significant new coverage of advances in satellite oceanography and results from new satellite missions, the second edition of this popular textbook introduces students to how remote sensing works, how to understand observations from Earth-observing systems, and the observations' importance to physical and biological oceanography. It provides full explanations of radiative transfer, ocean surface properties, satellite orbits, instruments and methods, visible remote sensing of biogeochemical properties, infrared and microwave retrieval of sea surface temperature, sea surface salinity retrieval, passive microwave measurements, scatterometer wind retrieval, altimetry and SAR. Also included are descriptions of the online archives where data can be obtained, and readers can obtain online tools for working with the data - enabling hands-on engagement with real-world observations. This is an ideal textbook for graduate and advanced undergraduate students in oceanography, remote sensing and environmental science, and a practical resource for researchers and professionals working with oceanographic satellite data.
Machine generated contents note: Preface; List of chemical symbols; List of mathematical symbols; List of abbreviations and acronyms; 1. Background; 2. Ocean surface phenomena; 3. Electromagnetic radiation; 4. Atmospheric properties and radiative transfer; 5. Reflection, transmission and absorption at the atmosphere/ocean interface; 6. Ocean color; 7. Infrared observations of sea surface temperature (SST); 8. Introduction to microwave imagers; 9. Passive microwave observations of the atmosphere and ocean surface; 10. Introduction to radars; 11. Scatterometers; 12. The altimeter; 13. Imaging radars; 14. Other missions: the gravity missions, ICESat-1 and -2, CryoSat-2, SMOS, Aquarius/SAC-D; Appendix: useful data tables; References; Index.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Oceanography -- Remote sensing